Fogo Island Goes Digital: Taking a Scholarly Journal On-line, the Case of CJC-Online.ca - Lorimer, Rowland and Smith, Richard and Wolstenholme, Paul (Canadian Journal of Communication, 2000)
An open-source software-based, on-line version of the Canadian Journal of Communication has been created by a group of scholars and students. This paper casts this activity as social science R&D with roots in development communications; as a viable alternative to control by aggressive profit-seeking commercial journal publishers; and as a transferable technology to other scholar-controlled journals. It describes the software used, the capacity of the software system developed, the dependence of the nature and speed of development on both technology and take-up by the user community, and the direction of future development.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjIwMDB2MjVuM2ExMTY1